Kościół, naród i państwo w perspektywie chrześcijańskiej. Refleksja ekumeniczna - Składanowski, Marcin (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
The article begins with a short presentation of the most important moments in the history of Christianity which have shaped complex relationship between contemporary Church, Nation and State. Then it shows the main issues regarding the relationship between Church and the national communities, as well as between Church and State. Finally, it indicates the implications of the different models of relationship between Church, Nation and State in the Polish social and religious context.